2015
DOI: 10.1080/13546805.2014.999915
|View full text |Cite
|
Sign up to set email alerts
|

Observable Social Cognition – A Rating Scale: an interview-based assessment for schizophrenia

Abstract: Introduction Individuals with schizophrenia consistently show impairments in social cognition (SC). SC has become a potential treatment target due to its association with functional outcomes. An alternative method of assessment is to administer an observer-based scale incorporating an informant’s “first hand” impressions in ratings. Methods The present study used the Observable Social Cognition: A Rating Scale (OSCARS) in 62 outpatients and 50 non-psychiatric controls (NPCs) to assess performance in domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 56 publications
0
31
0
1
Order By: Relevance
“…Coders were required to reach acceptable levels of inter-rater reliability (ICCs and Kappas > .70) on all interview-based measures, as well as the social skill role-play. Psychometric characteristics of all measures here as well as their means and standard deviations in this sample have been reported elsewhere (Healey et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Coders were required to reach acceptable levels of inter-rater reliability (ICCs and Kappas > .70) on all interview-based measures, as well as the social skill role-play. Psychometric characteristics of all measures here as well as their means and standard deviations in this sample have been reported elsewhere (Healey et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The Observable Social Cognition: A Rating Scale (OSCARS; Healey, Gibson, & Penn, ) is a rating scale of the participant's performance in a number of arenas related to social cognition, including, for example, correctly understanding others’ thoughts and intentions or jumping to conclusions. There are eight items with accompanying Likert scale responses (1 = no evidence of difficulty to 7 = evidence of extreme difficulty).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the OSCARS uniquely predicted real-world outcomes beyond objective social cognitive measures with a magnitude of nearly double the variance contributed by objective-based measures of social cognition. 27 On-going research for the fifth phase of the SCOPE trial suggested that informant based ratings on the OSCARs might be a stronger predictor of functional outcomes than performance on social cognitive performance-based assessments. In particular, OSCARs ratings generated by informants who were unaware of any elements of test performance or self-reports accounted for a larger proportion of the variation in social outcomes (all r = .53-.63, all R 2 = .25-36, p < .001) than non-social outcomes (r = .38, R 2 = .14, p < .001).…”
Section: Social Cognition Informant Ratingsmentioning
confidence: 99%